Wide range of age of onset and low referral rates to psychiatry in a large cohort of acne excoriée at a Swiss tertiary hospital. (3rd April 2018) - Anzengruber, Florian; Ruhwinkel, Katrin; Ghosh, Adhideb; Klaghofer, Richard; Lang, Undine E.; Navarini, Alexander A.
Abstract: Introduction: Repetitive skin manipulation is the key symptom in skin picking disorder (SPD) or acne excoriée des jeunes filles Brocq. The diagnostic and statistical manual of mental disorders (DSM-5) has recognized SPD as an independent disease, namely an obsessive-compulsive disorder. Thus, psychiatric treatment is indicated. Therefore, in a large cohort of SPD, we asked whether dermatologists' treatment strategy includes routine referrals to psychiatry. In addition, we describe epidemiological data, treatments and follow up. Methods: We performed a retrospective study, searching in our hospital database between January 1 2011 and December 31 2016. Results: A total of 154 (141 female, 13 male) patients were included in our study. In less than 5% a referral to a psychologist or psychiatrist occurred. More than 90% of all patients received topical and almost 40% systemical anti-acne treatment. The loss of follow-up was very high. Discussion: Our study shows that dermatologists focus on treating acne-like lesions in SPD, but rarely refer to psychiatry. Possible reasons include considerations of patients' reactions who often reject the idea of a psychological origin of the disease. Our results suggest that new treatment strategies should be created to address SPD correctly, i.e. by combined consultations with psychiatrists or specific training of dermatologists in psychiatric therapy and diagnostics.